2021
DOI: 10.3389/fpsyg.2021.751153
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Emotion Management for Personal Well-Being When Challenged by Their Online Work and Their Children's Online School

Abstract: Parents' emotional management was highly required during the COVID-19 lockdown, as juggling as their own job moved online and with being a parent of a child whose school was online proved to be a challenge for many. Our sample was restricted to parents who had to work online from their homes while their children had to attend school online, as external imposed conditions. The present study was based on Mayer and Salovey's theory and we aimed to investigate the relationship between parents' emotional intelligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…ECE current research have several studies on how parents can manage emotions when getting their children's personal assignments and homework online. Henter and Nastasa (2021) support the findings of this study so that as parents, they must be able to manage their time in carrying out their main work and accompanying children while studying at home to work cooperatively with teachers for home learning with each other (Harris, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…ECE current research have several studies on how parents can manage emotions when getting their children's personal assignments and homework online. Henter and Nastasa (2021) support the findings of this study so that as parents, they must be able to manage their time in carrying out their main work and accompanying children while studying at home to work cooperatively with teachers for home learning with each other (Harris, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, the mental health of mothers was affected by this new responsibility. It increased their levels of stress, anguish, tension, and loss of control [ 48 , 49 , 50 ]. There is evidence that the unequal distribution of labor and the exacerbation of traditional gendered roles during the lockdown impacted women’s health, especially their mental health: increased levels of stress and decreased personal satisfaction led to frustration and exhaustion [ 38 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 17 In a study investigating preschool, we showed that children were rated more hyperactive and had an overall decrease in child emotional–behavioural function during lockdown as compared with pre-lockdown, potentially due to parental stress in relation to the work–life balance. 18 19 Thus, forcing telework and home confinement of the entire family might have negative consequences on well-being and job performance 19 20 as shown by a French study investigating anxiety and depressive symptoms pre-COVID-19 lockdown, during the first wave and again during the second wave. 21 The study showed a continuing increase in mean scores of anxiety and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%